Effect of fish oil supplementation on plasma oxidant/antioxidant status in rats - Erdogan, H; Fadillioglu, E; Ozgocmen, S; Sogut, S; Ozyurt, B; Akyol, O; Ardicoglu, O (Churchill Livingstone, 2004)
The aim of this study was to investigate effect of dietary omega-3 fatty acid supplementation on the indices of in vivo lipid peroxidation and oxidant/antioxidant status of plasma in rats. The plasma thiobarbituric acid reactive substances (TBARS) and nitric oxide (NO) levels, and activities of xanthine oxidase (XO), superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) were studied in male Wistar Albino rats after ingestion of 0.4 g/ kg fish oil (rich in omega-3 fatty acids, eicosapentaenoic acid and docosahexaenoic acid) for 30 days and compared to untreated control rats. The rats in the treated group had significantly higher SOD activity (P < 0.001), NO levels (P < 0.01) and decreased TBARS levels (P < 0.05) with respect to controls whereas GSH-Px and XO activities were not significantly different between the groups. None of the measured parameters had significant correlation with each other in both groups. We conclude that dietary supplementation of omega-3 fatty acids may enhance resistance to free radical attack and reduce lipid peroxidation. These results support the notion that omega-3 fatty acids may be effective dietary supplements in the management of various diseases in which oxidant/antioxidant defence mechanisms are decelerated. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Acid Phenethyl Ester; N-3 Fatty-Acids; Lipid-Peroxidation; Alpha-Tocopherol; Eicosapentaenoic Acid; Docosahexaenoic Acid; Postmenopausal Women; Rheumatoid-Arthritis; Antioxidant Status; Omega-3-Fatty-Acids